ADSORPSI LIMBAH METHYLENE BLUE TERHADAP LIMBAH BIOMASSA NANASAdsorpsi Limbah Methylene Blue terhadap Limbah Biomassa Nanas - Monik Kasman; Asih Suzana; Allukman Nur Hakim (Jurnal Daur Lingkungan, 2022)
Dyes such as batik dyes and the textile industry can pollute the enviroment, especially receiving water bodies. The use of pineapple biomass waste as an adsorbent for removal of waste dyes (methylene blue). Adsorption experiment using pineapple biomass were varied in the adsorbent dose, contact time and stirring speed. In this study, the pineapple biomass adsorbent used consisted of pure and activated pineapple biomass. The experimental result showed that the adsorbent masses were varied into 0,5,1,2,5,3, dan 3,5 gr 250 mg/L glass, that the adsorbent mass does not affect color removal. Where the highest removal efficiency was 68%. The activated pineapple biomass adsorbent (AA) adsorbed more methylene blue waste than the unactivated pineapple biomass adsorbent (AM). While the contact time at the time of the trial consisted of 5 variations with a time span of 30,60,90,120 and 150 rpm, it was found that the higher the stirring speed the heigher the increase in efficiency of the experiment, the highest stirring was 72% at the stirring speed of 90 rpm. The isotherm suitable for the adsorption of methylene blue waste is the langmuir isotherm which allows the adsorbent to occur physically or chemically and is limited to the monolayer layer. The high ability of pineapple biomass as an adsorbent after being activated can reduse methylene blue waste by an average of 70% in terms of the adsorbent period, contact time and strring speed.